Local level inequalities in the use of hospital-based maternal delivery in rural South Africa - Silal, Sheetal Prakash; Bärnighausen, Till (Globalization and health, 2014)
There is global concern with geographical and socio-economic inequalities in access to and use of maternal delivery services. Little is known, however, on how local-level socio-economic inequalities are related to the uptake of needed maternal health care. We conducted a study of relative socio-economic inequalities in use of hospital-based maternal delivery services within two rural sub-districts of South Africa.
Gesehen am 05.03.2018